Reproductive health and the politics of abortion - Astrid Blystad (International Journal for Equity in Health, 2020)
Abstract This editorial provides an overview of a thematic series that brings attention to the persistently deficient and unequal access to sexual and reproductive health services for young women in sub-Saharan Africa. It represents an effort to analyze the multifaceted relationship between laws, policies and access to services in Ethiopia, Zambia and Tanzania. Using a comparative perspective and qualitative research methodology, the papers presented in this issue explore legal, political and social factors and circumstances that condition access to sexual and reproductive health services within and across the three countries. Through these examples we show the often inconsistent and even paradoxical relationship between the formal law and practices on the ground. Particular emphasis is placed on safe abortion services as an intensely politicized issue in global sexual and reproductive health. In addition to the presentation of the individual papers, this editorial comments on the global politics of abortion which represents a critical context for the regional and local developments in sexual and reproductive health policy and care provision in general, and for the contentious issue of abortion in particular.